(untitled) (Homoeopathy for All, 2025)
Acne is one of the most common skin conditions of all age group individuals especially among the teenagers. The clinical presentation of acne can range from a mild comedonal form to severe inflammatory cystic acne of the face, chest, and back. Acne can occur during a time of low self-esteem and high concern about appearance. This article reviews about causes, risk factors, different types, clinical presentation, general management including some home remedies and homoeopathic way of treatment of acne. Homoeopathy treats the person as a whole. It means that homoeopathic treatment focuses on the patient as a person, as well as his pathological condition.